Validation and User Experience Study of INDDEX24, a Novel Global Dietary Assessment Platform in Burkina Faso and Viet Nam. (29th May 2020) - Bell, Winnie; Coates, Jennifer; Some, Jerome; Colaiezzi, Brooke; Wafa, Sarah; Do, Ha; Zeba, Augustin; Prata, Cathleen; Beatrice, Rogers
Abstract: Objectives: This study assessed the accuracy and user experience of the INDDEX24 platform compared to a traditional pen and paper (PAPI) 24HR in Burkina Faso and Viet Nam. INDDEX24 is a dietary assessment platform, developed by the International Dietary Data Expansion (INDDEX) Project, which links a tablet-based platform for conducting individual 24HR to a set of web-based dietary data inputs (food composition database, standard recipes, conversion factors). Methods: We used quantitative and qualitative methods. INDDEX24 and PAPI 24HR modalities were compared against the benchmark method, Weighed Food Records (WFR). Outcomes were energy intake, macronutrients, select micronutrients, and food groups. To assess the user experience, we conducted focus groups with field staff, who also completed a short questionnaire. Needed sample size was 234 women, 117 for each arm, based on Pearson's correlation >0.6 with type I error set at 5% and power at 80%. Data collection included a full day of direct observation for the WFR, followed by a single 24HR. Socio-demographic data were also collected. Quantitative data were analyzed with Stata v15.1; qualitative data with NVivo 11. Results: A total of 231 rural women in Burkina Faso and 234 rural women in Viet Nam, aged 18–49 years, were enrolled August-October 2019 and assigned to a study arm. Mean (±SD) age of participants was 29.7 (±8.4) (Burkina Faso) and 35.2 (±8.3) years (Viet Nam). Most respondents in Viet Nam completed some secondary school or higher (94.9%); in Burkina Faso most respondents (83.4%) had no formal education; 3.2% had secondary school level or higher. There were no statistically significant differences in age, education, pregnancy, and breastfeeding status between the two arms in either country. Field staff preferred using INDDEX24 to PAPI and provided some suggestions for improvement. Conclusions: The study was successfully implemented in Burkina Faso and Viet Nam. The required sample size was obtained with balanced study arms. Qualitative feedback from field staff confirmed the superiority of INDDEX24 from a user perspective. The results will be important for fine tuning INDDEX24 for future use. The set of dietary data inputs developed for this study will remain in the public domain and be useful for researchers, saving time and cost for future surveys. Funding Sources: Bill and Melinda Gates Foundation.